Impact of Blood Sample Collection and Processing Methods on Glucose Levels in Community Outreach Studies. (10th January 2013) - Turchiano, Michael; Nguyen, Cuong; Fierman, Arthur; Lifshitz, Mark; Convit, Antonio
Abstract : Glucose obtained from unprocessed blood samples can decrease by 5%–7% per hour due to glycolysis. This study compared the impact of glucose degradation on measured glucose values by examining two different collection methods. For the first method, blood samples were collected in tubes containing sodium fluoride (NaF), a glycolysis inhibitor. For the second method, blood samples were collected in tubes containing a clot activator and serum gel separator and were centrifuged to separate the serum and plasma 20 minutes after sample collection. The samples used in the two methods were collected during the same blood draw and were assayed by the clinical laboratory 2–4 hours after the samples were obtained. A total of 256 pairs of samples were analyzed. The average glucose reading for the centrifuged tubes was significantly higher than the NaF tubes by 0.196 ± 0.159  mmol/L (P < 0.01 ) or 4.2%. This study demonstrates the important role collection methods play in accurately assessing glucose levels of blood samples collected in the field, where working environment may be suboptimal. Therefore, blood samples collected in the field should be promptly centrifuged before being transported to clinical labs to ensure accurate glucose level measurements.